A search for Secluded Dark Matter in the Sun with the ANTARES neutrino telescope - Adrian-Martiez, S.; Albert, A.; Andre, M.; Anton, G.; Ardid, M.; Aubert, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, S.; et al. (Institute of Physics Publishing, 2016)
A search for Secluded Dark Matter annihilation in the Sun using 2007–2012 data of the ANTARES neutrino telescope is presented. Three different cases are considered: a) detection of dimuons that result from the decay of the mediator, or neutrino detection from: b) mediator that decays into a dimuon and, in turn, into neutrinos, and c) mediator that decays directly into neutrinos. As no significant excess over background is observed, constraints are derived on the dark matter mass and the lifetime of the mediator.